2015
DOI: 10.1136/vr.102993
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type A as an adjunct in postoperative pain management in dogs undergoing radical mastectomy

Abstract: The aim of this randomised placebo-controlled, observer-blinded study was to evaluate the analgesic effects of botulinum toxin type A (BoNT-A) as an adjunct for postoperative pain control in dogs. Sixteen dogs undergoing bilateral radical mastectomy for treatment of mammary tumours were enrolled. Twenty-four hours before surgery, the subjects were distributed into two groups of eight dogs each: 7 iu/kg BoNT-A (BoNT-A) or saline (Control) was administered subcutaneously in each mammary gland. Following sedation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…For example, in rats, intraplantar or intrathecal injection of onaBoNT-A significantly reduced the cumulative post-surgical pain score–a measure of non-evoked pain based on the position of the operated paw in relation to the cage floor 22 . Also, aboBoNT-A reduced non-evoked postoperative pain and need for rescue analgesia in dogs undergoing radical bilateral mastectomy 23 . Overall, the analgesic efficacy of aboBoNT-A in the post-surgical pain pig model is well aligned with few examples of its use in the clinic.…”
Section: Discussionmentioning
confidence: 91%
“…For example, in rats, intraplantar or intrathecal injection of onaBoNT-A significantly reduced the cumulative post-surgical pain score–a measure of non-evoked pain based on the position of the operated paw in relation to the cage floor 22 . Also, aboBoNT-A reduced non-evoked postoperative pain and need for rescue analgesia in dogs undergoing radical bilateral mastectomy 23 . Overall, the analgesic efficacy of aboBoNT-A in the post-surgical pain pig model is well aligned with few examples of its use in the clinic.…”
Section: Discussionmentioning
confidence: 91%
“…Aiyama (1973) [30] reported that through communications with the intercostobrachial nerve, the MPN may contain sensory fibers distributed to ventral surfaces of the arm, thoracic wall near the axilla, and inferolateral part of the pectoralis major. A few studies have reported pectoralis muscle spasm as a source of chest wall pain after tissue expander reconstruction [31] and radical mastectomy [32]. Studies have described a pectoral nerve block for use in patients undergoing subpectoral breast augmentation [10,23,33].…”
Section: Discussionmentioning
confidence: 99%
“…Other than for osteoarthritic pain, the analgesic effect of BoNT-A (Dysport) was tested in post-operative bilateral radical canine mastectomy and showed usefulness as an adjuvant antinociceptive agent to control pain, effective when injected prior to surgery [ 62 ]. By inhibiting the release of neuropeptides at the nociceptive nerve endings, BoNT-A lowers directly peripheral, and indirectly central sensitivity, providing analgesia.…”
Section: Therapeutic Applications In Veterinary Medicinementioning
confidence: 99%